2017
DOI: 10.4103/1008-682x.184271
|View full text |Cite|
|
Sign up to set email alerts
|

Combination of low-energy shock-wave therapy and bone marrow mesenchymal stem cell transplantation to improve the erectile function of diabetic rats

Abstract: Stem cell transplantation and low-energy shock-wave therapy (LESWT) have emerged as potential and effective treatment protocols for diabetic erectile dysfunction. During the tracking of transplanted stem cells in diabetic erectile dysfunction models, the number of visible stem cells was rather low and decreased quickly. LESWT could recruit endogenous stem cells to the cavernous body and improve the microenvironment in diabetic cavernous tissue. Thus, we deduced that LESWT might benefit transplanted stem cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 54 publications
0
21
0
1
Order By: Relevance
“…After the 12-week treatment, erectile function was assessed using intracavernosal pressure (ICP) and mean arterial pressure (MAP) tests as previously reported [12]. Briefly, while under anesthesia, the bilateral cavernous nerves were exposed and a bipolar steel electrode was used for nerve stimulation.…”
Section: Erectile Function Evaluationmentioning
confidence: 99%
“…After the 12-week treatment, erectile function was assessed using intracavernosal pressure (ICP) and mean arterial pressure (MAP) tests as previously reported [12]. Briefly, while under anesthesia, the bilateral cavernous nerves were exposed and a bipolar steel electrode was used for nerve stimulation.…”
Section: Erectile Function Evaluationmentioning
confidence: 99%
“…Therefore, the validity and durability of stem cell therapy in the clinic requires further investigation. Additionally, antioxidant and Li‐ESWT therapies have been explored in animal experiments, exerting particular influence in anti‐inflammatory responses and improving endothelial function (Shan et al ., ). In recent years, several studies have highlighted the therapeutic potential of, and the underlying mechanism for, the involvement of endogenous stem cells (SCs) in these two treatments.…”
Section: Discussionmentioning
confidence: 97%
“…There have been several reports describing the combination of adipose-derived MSCs with penile shock wave in a Racine model demonstrating positive effects on the cavernosal tissue [9,36,37]. In one such study, combination treated penile tissue showed significantly increased levels of cavernous nerve beta-III tubulin expression, smooth muscle actin, neural and endothelial NOS nitric oxide synthase, cGMP, and reduced cavernosal apoptotic index [37].…”
Section: Discussionmentioning
confidence: 99%